DTASR: Dual Threshold-based authentication for secure routing in mobile adhoc network - Khan, Burhan ul Islam; Olanrewaju, Rashidah Funke; Baba, Asifa Mehraj; Mir, Roohie Naaz; Lone, Sajad Ahmad (Institute of Information System & Research Center ( IISRC), 2015)
The Mobile Adhoc Network ( MANET) is not only limited to the temporary rescue operations rather it has been conceptualized to be adopted into many civil society comfort and safety applications. The self-configurability of MANET’s node is the root cause of vulnerability and security threats, thus there is a need of light weight protocols which can ensure optimal Quality of Service (QoS) in secure way of routing. This paper projects a model of such secure routing in MANET called DTASR i.e. Dual Threshold-based Authentication for Secure Routing accentuating upon a resource-based threshold scheme as well as trust-based authentication scheme to ensure higher degree of resiliency against adversaries. The proposed illustrates an enhanced ability of communication performance when compared to conventional secure routing schemes.